Bringing home a piece of our past. (June 2018) - Tasker, Elizabeth
The Hayabusa2 spacecraft will soon rendezvous with asteroid Ryugu in order to study its composition using remote sensing, a lander, rovers and sample return, explains Elizabeth Tasker.